P630Calmodulin/CaMKII inhibition accelerates conduction velocity by augmenting the localization of Cx43 in the intercalated disk. (15th July 2014) - Van Veen, A; Takanari, H; Bourgonje, V; Fontes, MSC; Raaijmakers, HAJ; Driessen, H; Van Der Heyden, MAG; Van Rijen, HVM; Kodama, I; Vos, MAG
Abstract: Purpose: In healthy hearts, ventricular gap junctions are composed by Connexin43 proteins (Cx43) and are localized in the intercalated disk (ID) where they enable appropriate electrical and metabolic coupling. During pathophysiological conditions, Cx43 is heterogeneously downregulated whereas the activity of CaM/CaMKII signaling increases. It is unclear if CaM/CaMKII affects the expression or the trafficking of Cx43. We analyzed several different models to assess the influence of CaM/CaMKII inhibition on Cx43 gap junctions and conduction properties of the heart. Methods: AC3-I mice, in which CaMKII was genetically inhibited, were subjected to pressure overload (16 wks, TAC vs sham) to evaluate the effect of chronic inhibition of CaMKII under pathological conditions. Conduction velocity (CV) was measured by high-resolution optical mapping and epicardial mapping on Langendorff perfused rabbit and AC3I mouse hearts respectively. Intercellular communication between cultured neonatal rat cardiomyocytes (CMs) was assessed by a dye transfer assay. Subcellular expression of junctional Cx43 from rabbit ventricles and cultured dog cardiomyocytes was evaluated by Triton X-100-based fractionation and Western blot (WB). Subcellular distribution of Cx43 in perfused rabbit and mouse ventricles was evaluated by immunohistochemistry. Results: In mice, CV was augmented in AC3-I sham (n=11, p<0.05 vs. WT) and preserved after TAC in the AC3-I mice (n=11), but impaired in TAC-WT mice (-20%). The expression of Cx43 was preserved after TAC surgery in AC3-I mice though arrhythmias were still present as was increased fibrosis. W7 (CaM inhibitor, 10 μM) significantly increased CV (+8%, n=4, p<0.05 vs. control) in rabbits while susceptibility to arrhythmias decreased. Immuno-confocal microscopy revealed enlarged Cx43 cluster sizes in the ID of W7 treated rabbit hearts. Total amount of Cx43 did not change by W7 (n=5), whereas junctional Cx43 increased (+10%, n=5, p<0.05). These data were confirmed in cultured dog cardiomyocytes both via treatment with W7 and KN93, (CaMKII inhibitor, 1-10 μM). Dye coupling in rat CMs improved (+37.5%, n=7, p<0.05 vs. control). Conclusion: Both acute and chronic CaM/CaMKII inhibition positively affects conduction properties and localization of Cx43 in ID. Only in absence of pathological fibrosis this reduced the susceptibility for arrhythmias.